Implementasi Bimbingan Teknis (Bimtek) Fasilitator Inovasi Daerah - Ray Septianis Kartika; Garsy Simorangkir (Badan Riset dan Inovasi Daerah Provinsi Kalimantan Selatan, 2019)
Many things must be addressed in improving competitiveness, namely improving the quality of human resources and meeting the supporting facilities. BPP Kemendagri seeks to change the mindset of ASN in interpreting regional innovation, as well as fulfilling service infrastructure. BPP Kemendagri fulfills both of these by conducting facilitator training aimed at fixing the concept of ASN thinking on regional innovation and increasing ASN's expertise in operating 7 services, namely population, education, health, employment, commodities, DPRD and licensing.. The purpose of this study is to examine the effectiveness of the technical guidance as well as the competence of resource persons involved in it. This research method is quantitative and qualitative using a Likert scale. The results of the study showed that the implementation of training 70% was carried out effectively. The competence of training resource persons for Creative Ideas Material was considered to be very effective (90.48%), the Regional Innovation Policy material was considered effective (70.6%), the material for the Acceleration of Regional Innovation Program Strategy, Challenges and Developments and Infographic Design with Power Point was considered quite effective (53.69%), while the Puja Indah material was considered to be very ineffective (11.97%). The recommendation given is the consistency of BPP Kemendagri in increasing the capacity of ASN in the area of ​​regional innovation in terms of determining the material, determining the sources and determining the training participants. BPP Kemendagri can collaborate with the BPSDM Kemendagri in compiling technical standards for the implementation of the Regional Innovation Facilitator Technical Guidance which is used as a guideline for training implementation, so that the technical guidance is more structured and the level of effectiveness can be measured. Abstrak Bimtek fasilitator inovasi daerah adalah kegiatan yang dilakukan BPP Kemendagri dalam melakukan pembinaan inovasi daerah. Bimtek ini dilakukan setiap setahun sekali dengan mengundang peserta yang berasal dari Provinsi/Kabupaten/Kota. Pelaksanaan bimtek ini, ingin mewujudkan fasilitator yang dapat mengoperasionalkan aplikasi terintegrasi dengan tujuh layanan yaitu kependudukan, pendidikan, kesehatan, ketenagakerjaan, komoditi, DPRD dan perijinan. Untuk itulah bimtek dilakukan, sebagai proses pembelajaran bagi fasilitator dalam mendampingi Organisasi Perangkat Daerah. Tujuannya adalah untuk melihat pelaksanaan bimtek dan kompetensi narasumber yang dilibatkan. Metode kajian secara kuantitatif dan kualitatif dengan menggunakan skala likert. Hasil kajian menyebutkan bimtek fasilitator inovasi daerah sudah dijalankan dengan efektif dengan presentase 70 %. Sedangkan kompetensi narasumber bimtek fasilitator inovasi daerah untuk materi kebijakan inovasi daerah dinilai efektif (70,6%), materi Strategi Percepatan Program Inovasi Daerah, Tantangan dan Perkembangan serta Infografis design with power point dinilai cukup efektif, materi puja indah dinilai sangat tidak efektif dan materi ide kreatif dinilai sangat efektif (90,48 %). Sarannya adalah (1) BPP kemendagri dapat bekerjasama dengan BPSDM kemendagri dalam membangun bimtek, (2) melakukan kajian lanjutan dengan fokus pada perbaikan materi di tahun mendatang, (3) melibatkan akademisi, best practise daerah dan bisnis sebagai narasumber, (4) melakukan pre test di awal pelaksanaan bimtek. Dengan demikian bimtek yang sudah dilaksanakan dapat lebih prosefional, akademis dan dapat bermanfaat